Reforma trabalhista de 2017: a ampliação da exploração da força de trabalho no contexto das políticas neoliberais - Zanghelini, Fabrício André (2020)
Within a national and world context of attack on workers' rights, in July 2017, without a democratic debate with civil society, was approved by the National Congress and sanctioned by the President of the Republic Law 13,467 / 2017, which materialized the called Labor Reform - the most profound change in labor relations since the Consolidation of Labor Laws (CLT) in 1943. It is imperative to note that this reform is presented, in the neoliberal view, as a possibility of modernization of labor relations. However, it verifies the essence of production relationships is increases the exploitation of the workforce. In this sense, from the analysis of the fact that labor reform seeks to increase the power of capital (greater ability to determine the conditions of hiring, use and remuneration of the workforce), the objective of this research is to analyze the labor reform of 2017 in the historical (and current) context of neoliberal policies and to verify how their results - after, practically, two years after the consolidation of such reform - have repercussions on the labor market and on the working class. Using historical-dialectical materialism as a scientific method, it is an explanatory research that aims to identify the results and effects of the 2017 labor reform from a theoretical and empirical perspective. Thus, in the procedure analysis, the theoretical-bibliographical and documentary study supported by Marx and several authors who present a critical perspective are adopted. As for the empirical analysis of the observed phenomena, descriptive statistics is used, having as source of research the original data from the National Continuous Household Sample Survey (PNADC/IBGE) and the General Register of Employed and Unemployed (CAGED). Finally, the 2017 labor reform, which eased (withdrew) various rights historically imposed by the working class struggle and lowered the total cost of labor on the promise of modernizing labor relations and creating new jobs, did worsen the employment and informality and, furthermore, it encouraged hiring and occupation that increase the precariousness of work and the exploitation of the workforce in Brazil.